Diseño de un modelo de red de zona perimetral segura para pymes del valle Jequetepeque - Sánchez Quiroz, Bertha Natalí (2013)
Currently the subject of computer security for small and medium businesses evolve rapidly in our country, being necessary to protect our information from attack either internal or external._x000D_ This paper proposes the design of a network model for SMEs secure perimeter zone Jequetepeque Valley, revealing a collection of the aspects most relevant security technology that SMEs currently employ to maximize the benefits Internet offers. It is noted that for safety, it is important that the infrastructure and information resources of the organization must be protected by a security scheme that reduces the levels of vulnerability._x000D_ There are a lot of methods for securing a computer network, one of the most used is the DMZ 'or demilitarized zones. A DMZ or perimeter network is a local network that sits between an organization's internal network and an external network, with the aim that the connections from the internal and external network to the DMZ are permitted, while connections from the DMZ only allow the external network. For the use of security technologies to be effective, must be reinforced by safety standard ISO 17799 and implementing security policies, to define a general framework, methods, procedures and mechanisms of how to handle security for resources, services and systems within SMEs